2021
DOI: 10.32725/kont.2021.017
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family intervention programs on the caregiver burden of hemodialysis patients

Abstract: Aim: Family caregivers of hemodialysis patients play a vital role in the health sector. However, the care they provide (especially over a long period of time) can cause fatigue, stress, and create a burden for them. Therefore, the aim of this review is to evaluate the effect of family intervention programs in reducing the burdens of family caregivers. Methods: This is a systematic review, and the database used in the article search included EBSCO, ProQuest, and PubMed (using relevant keywords based on the topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…In the review article of Surani, (12) In a study conducted by Qane, (33) the results showed the effectiveness of supportive educative program on the burden on family caregivers of hemodialysis patients. Since the level of caregiver burden in caregivers of hemodialysis patients is high and these pressures can reduce the level of care for these patients and also endanger the caregiver's physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the review article of Surani, (12) In a study conducted by Qane, (33) the results showed the effectiveness of supportive educative program on the burden on family caregivers of hemodialysis patients. Since the level of caregiver burden in caregivers of hemodialysis patients is high and these pressures can reduce the level of care for these patients and also endanger the caregiver's physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is a close relationship between the health of caregivers and patients and caregivers can play a significant role in the health and improvement of their hemodialysis patients. Studies show that some interventions such as psycho-educational intervention, (11) family intervention programs, (12) psychosocial Support (5) are effective in reducing the caregiver burden in caregivers of hemodialysis patients. Since the learning and teaching Benson's relaxation method is easy and requires no specific knowledge and skills and can easily be done by the caregivers of hemodialysis patients and considering the important role of caregivers in the process of caring for hemodialysis patients and the limited studies on the effect of BRT on reducing caregiver burden in this group of caregivers, therefore the present study aims to determine the effect of BRT on caregiver burden in caregivers of hemodialysis patients.…”
Section: Introduction Cmentioning
confidence: 99%
“…Nyeri telah menjadi keluhan utama yang paling sering dirasakan oleh penderita kanker serta menjadi alasan paling umum untuk mencari dan mendapatkan bantuan medis (Sari, Suza, & Tarigan, 2021). Menurut Budi S tahun 2020 Nyeri diartikan sebagai suatu kondisi yang tidak menyenangkan yang dialami oleh seseorang yang akan memicu timbulnya rasa sakit.…”
Section: Pendahuluanunclassified
“…Intervensi pendidikan dan psikologis dapat membantu mengurangi beban pengasuh keluarga (caregiver) ketika merawat pasien hemodialisis (Surani et al, 2021). Terdapat hubungan yang erat antara orang yang mengalami dialisis dan keluarga yang merawatnya, maka keluarga sangat di butuhkan dalam merawat pasien hemodialisis (Sousa et al, 2023).…”
unclassified